2007
DOI: 10.1038/sj.ejhg.5201884
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of XRCC1 predicts overall survival of gastric cancer patients receiving oxaliplatin-based chemotherapy in Chinese population

Abstract: Pharmacogenetic advances in cancer chemotherapy have the potential to predict clinical benefit to particular regimens. Platinum agents have shown to be effective in the treatment of gastric cancer. We assessed whether single nucleotide polymorphisms (SNPs) in xeroderma pigmentosum group D (XPD), X-ray repair cross complementing group 1 (XRCC1) and glutathione S-transferase P1 (GSTP1) predicted overall survival in gastric cancer patients receiving oxaliplatin-based chemotherapy in Chinese population. SNPs of XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 32 publications
2
24
2
Order By: Relevance
“…No homozygous carriers of the glutamine allele (XRCC1 399Gln/Gln) were detected in this study, which is not consistent with previous reports [41,42]. It is possible that an unknown region that contributes to the potential mechanism by which the XRCC1Arg399Gln polymorphism affects the outcome as well as the classification of tumour may have led to these inconsistent results [40,41,43]. …”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…No homozygous carriers of the glutamine allele (XRCC1 399Gln/Gln) were detected in this study, which is not consistent with previous reports [41,42]. It is possible that an unknown region that contributes to the potential mechanism by which the XRCC1Arg399Gln polymorphism affects the outcome as well as the classification of tumour may have led to these inconsistent results [40,41,43]. …”
Section: Discussioncontrasting
confidence: 95%
“…Moreover, a switch from arginine to glutamine in cells, such as Arg/Gln or Gln/Gln, negatively affected the DNA repair activity, which was expected to lead to a better response to platinum-based chemotherapy [37,38]. The XRCC1 Arg399Gln genotype has been shown to be a favourable prognostic factor in cervical cancer patients treated with platinum-based chemotherapy [39], although a conflicting result was reported showing that the XRCC1 Arg399Gln genotype was associated with significantly lower survival in gastric cancer patients [40]. In the present study, the XRCC1 Arg399Gln arginine allele was associated with no favourable survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed significantly better progression-free survival for XRCC1Arg399Arg than for A/G and G/G types. Similarly, Liu et al [31] investigated 62 gastric cancer patients and found better OS in XRCC1A/A than in G/A and G/G types. These results were consistent with ours.…”
Section: Discussionmentioning
confidence: 95%
“…In vitro, tumour cells expressing the XRCC1Arg399Gln (Gln) AA genotype are more resistant to a variety of anticancer drugs including alkylating agents (carboplatin and cisplatin), DNA/RNA anti-metabolites (5-fluorouracil) and antimitotics (vinblastine) [13] although it has also been associated with decreased repair [3,14,15]. Other clinical studies have reported an association of the XRCC1Arg399Gln AA genotype or A allele with decreased survival or poor treatment response for patients with esophageal [16], gastric [17], non-small cell lung [12,18], colorectal [19] and cervical cancer [20]. Interestingly, the CGA haplotype or the AA genotype of XRCC1Arg399Gln was associated with increased risk for bladder cancer recurrence following BCG immunotherapy [21].…”
Section: To the Editormentioning
confidence: 99%